PROTES PEREMPUAN TERHADAP KONSTRUKSI GENDER DALAM KARYA LUKIS - Fariko Edwardi; Erfahmi .; Zubaidah . (Universitas Negeri Padang, 2012)
ABSTRACT Protest women against gender inequality began to emerge. This is evident from women is behavior in everyday life, ranging from the mindset, how to dress, and determine the way of life they want to pass. For example, at this time women have started to compete for equal position with men as the party office, legislators, and even the president. Creating the works of art aim to demonstrate the role of women in the profession in terms of painting, visualize profession women equal to men in paintings, to visualize the behavior of women who do not distinguish gender in paintings. For example, in using the form on the symbol, either object or figure women themselves, the authors attempt to make it simpler.